2017
DOI: 10.1016/j.envint.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Parental occupational exposure to benzene and the risk of childhood cancer: A census-based cohort study

Abstract: Background: Previous studies on occupational exposures in parents and cancer risks in their children support a link between solvents and paints with childhood leukaemia. Few studies have focused specifically on benzene.Objectives: To examine whether parental occupational exposure to benzene is associated with an increased cancer risk in a census-based cohort of children.Methods: From a census-based cohort study in Switzerland, we included children aged <16 years at national censuses (1990, 2000). We retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…Other potential risk factors include genetic causes, higher birth weight and parental age, increased infections, exposure to pesticides and traffic-related air pollution, as well as parental exposure to benzene. 47-49 However, the results of this study do not allow us to draw conclusions about specific risk factors that may have contributed to the overall increasing incidence of cancer in general, and specifically of leukaemia and CNS tumours.…”
Section: Discussionmentioning
confidence: 71%
“…Other potential risk factors include genetic causes, higher birth weight and parental age, increased infections, exposure to pesticides and traffic-related air pollution, as well as parental exposure to benzene. 47-49 However, the results of this study do not allow us to draw conclusions about specific risk factors that may have contributed to the overall increasing incidence of cancer in general, and specifically of leukaemia and CNS tumours.…”
Section: Discussionmentioning
confidence: 71%
“…Other potential risk factors include genetic causes, higher birth weight and parental age, increased infections, exposure to pesticides and traffic-related air pollution, as well as parental exposure to benzene. [47][48][49] However, the results of this study do not allow us to draw conclusions about specific risk factors that may have contributed to the overall increasing incidence of cancer in general, and specifically of leukaemia and CNS tumours.…”
Section: Possible Reasons For Increasing Trend In Incidencementioning
confidence: 74%
“…As also for the permanent transit of this type of automotive in this area, due to the loading and unloading of merchandise in the industrial sources that are in this industrial agglomerate. Likewise, in this area of industrial agglomerate the exhibition may not be related to air emissions but to the occupational exposure of parents who live near the workplace; there are several authors who have found a relationship between childhood cancer and maternal or paternal occupation [40] [41] [42] [43] [44].…”
Section: Discussionmentioning
confidence: 99%